Is Subsidizing Companies in Difficulties an Optimal Policy? An Empirical Study on the Effectiveness of State Aid in the European Union - Nicole Nulsch (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2014)
Even though state aid in order to rescue or restructure ailing companies is regularly granted by European governments, it is often controversially discussed. The aims for rescuing companies are manifold and vary from social, industrial and even political considerations. Well-known examples are Austrian Airlines (Austria) or MG Rover (Great Britain). Yet, this study aims to answer the question whether state aid is used effectively and whether the initial aim why aid has been paid has been reached, i.e. the survival of the company. By using data on rescued companies in the EU and applying a survival analysis, this paper investigates the survival rates of these companies up to 15 years after the aid has been paid. In addition, the results are compared to the survival rates of non-rescued companies which have also been in difficulties. The results suggest that despite the financial support, business failure is often only post-poned; best survival rates have firms with long-term restructuring, enterprises in Eastern Europe, smaller firms and mature companies. However, non-funded companies have an even higher ratio to go bankrupt.
urn:nbn:de:gbv:3:2-30837
Keywords: K21; L49; L59; 330; European competition policy; state aid; firm survival; survival analysis; control group